2011
DOI: 10.3988/jcn.2011.7.4.210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lacunar Infarctions on Cognitive Impairment in Patients with Cerebral Autosomal-Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy

Abstract: Background and PurposeCerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited microangiopathy caused by mutations in the Notch3 gene. Although previous studies have shown an association between lacunar infarction and cognitive impairment, the relationship between MRI parameters and cognition remains unclear. In this study we investigated the influence of MRI parameters on cognitive impairment in CADASIL.MethodsWe applied a prospective protocol to 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
3
17
1
3
Order By: Relevance
“…Cognitive impairment in CADASIL is similar to that reported for sporadic subcortical ischemic vascular dementia and is thought to the result of dysfunction within the subcortical/frontal network due to the leukoaraiosis, although a multi‐infarction origin based on the accumulation of cerebral infarcts was also proposed . Cognitive decline preceding strokes is unusual in CADASIL, but several cases were reported .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Cognitive impairment in CADASIL is similar to that reported for sporadic subcortical ischemic vascular dementia and is thought to the result of dysfunction within the subcortical/frontal network due to the leukoaraiosis, although a multi‐infarction origin based on the accumulation of cerebral infarcts was also proposed . Cognitive decline preceding strokes is unusual in CADASIL, but several cases were reported .…”
Section: Discussionsupporting
confidence: 63%
“…Our report suggest to consider CADASIL in those cases with recurrent TGA, especially when MRI shows multifocal hyperintensities affecting the cerebral white matter or when it is followed by cognitive decline. Cognitive impairment in CADASIL is similar to that reported for sporadic subcortical ischemic vascular dementia and is thought to the result of dysfunction within the subcortical/frontal network due to the leukoaraiosis, although a multi-infarction origin based on the accumulation of cerebral infarcts was also proposed [5,13,14]. Cognitive decline preceding strokes is unusual in CADASIL, but several cases were reported [1,3,4].…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies that examined the relationship between CMB and cognitive impairment showed mixed results; with some reporting significant associations [36, 37] and others were not significant [38, 39]. Our sample had a lower prevalence of CMB compared to studies in developed countries (18–38%) [40], which might reflect regional or lifestyle differences that need to be further examined.…”
Section: Discussionmentioning
confidence: 50%
“…[ 2 ] The main clinical manifestations are recurrent stroke, cognitive decline, chronic headache, mood disturbances, and seizure. [ 3 , 4 ] Magnetic resonance imaging (MRI) is crucial in the diagnosis of CADASIL. Typical MRI findings include multiple subcortical lacunes, extensive white matter change, and multiple cerebral microbleeds (CMBs).…”
Section: Introductionmentioning
confidence: 99%